Harmony of Danglung Music: The Expansion of Danglung Traditional Music as a Medium of Syi’ar Shalawat - Firdausi, Putri Nadiyatul; Arifin, Zainul; As’at, As’at (Proceedings of Annual Conference for Muslim Scholars, 2024)
Danglung music is a traditional music of the Madurese ethnicity in Pandalungan, which later expanded as a medium for syi’ar shalawat. This study aims to explore the expansion of danglung music as a medium for shalawat in the pandalungan area to create cultural and religious harmony. The results showed that the expansion of danglung music as a medium for syi’ar shalawat was carried out since 2000, spearheaded by one of the Lumajang cultural preservation organizations CIO Indonesian Art Culture. The expansion of danglung music as a media for syi’ar shalawat has benefits in addition to revitalizing and preserving traditional danglung music as well as being an effective and acceptable syi’ar media in the community.